The Effectiveness of Individual Performance Commitment Review Form as an Evaluation Tool to Improve Teachers’ Performance: Basis for Technical Assistance - Cadag, Christopher E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
A well-structured evaluation such as Individual Performance Commitment and Review Form (IPCRF) can provide valuable feedback to teachers and contribute to their growth and effectiveness. This study aims to assess the effectiveness of the IPCRF as an evaluation tool for improving teachers' performance. This study utilized the mixed method approach particularly the sequential exploratory, blending both qualitative and quantitative research methods. The participants of the study were 59 composed of teachers and school heads from selected schools in Casiguran District 2. The qualitative phase of this research relied on semi-structured interview guides. For the quantitative phase, a researcher-made survey questionnaire was utilized. Results revealed that teachers were rated primarily as having performed outstandingly. However, the level of effectiveness of IPCRF in assessing the teachers’ performance, as assessed by school heads and teachers, is low in terms of the plus factor. School heads need to provide forms of technical assistance to the teachers, to ensure that necessary resources, such as teaching materials or technology, are made available to support teachers' improvement efforts. Meanwhile, the issues and concerns encountered by the teachers, as assessed by school heads and teachers, are high as to work performance. Thus, the proposed in-house feedback session aims to improve teachers’ performance through the provision of technical assistance. School heads and teachers may participate in seminars and training sessions offered by Department of Education (DepEd) officials in conjunction with teachers to improve their comprehension of the IPCRF.